2018
DOI: 10.31223/osf.io/vr9z7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary microplastics were prevalent in sediment in a freshwater UK urban river

Abstract: 29 30Plastic pollution has been documented in terrestrial and aquatic environments worldwide, with 31 growing concern for 'microplastics' (MPs, <5 mm). Understanding of the sources, fate, and impact of 32MPs remains limited, particularly in freshwater environments. Furthermore, their small sizes and a 33 lack of standardised methodology hinders monitoring and risk assessment of these emerging 34 contaminants. Here, the distribution of microscopic debris in an urban river close to the marine 35 environment in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The study revealed that the number of MPs found in the surface water of the river in the Tibet Plateau ranged from 483 to 967 items per cubic meter, whereas the amount found in the sediment ranged from 50 to 195 pieces per kilogram (Jiang et al, 2019). Meanwhile, another study that investigated the amount and distribution of primary and secondary MPs in an urban river near the coastal environment in the West of Scotland found that 88% of the overall counts comprised the major fiber type, which ranged from 161 to 432 MPs kg −1 dry sediment (Blair et al, 2019). However, the presence of fibers in the blanks suggests that air contamination may have played a role.…”
Section: Accumulation and Abundance Of Microplastics In Aquatic Envir...mentioning
confidence: 99%
See 2 more Smart Citations
“…The study revealed that the number of MPs found in the surface water of the river in the Tibet Plateau ranged from 483 to 967 items per cubic meter, whereas the amount found in the sediment ranged from 50 to 195 pieces per kilogram (Jiang et al, 2019). Meanwhile, another study that investigated the amount and distribution of primary and secondary MPs in an urban river near the coastal environment in the West of Scotland found that 88% of the overall counts comprised the major fiber type, which ranged from 161 to 432 MPs kg −1 dry sediment (Blair et al, 2019). However, the presence of fibers in the blanks suggests that air contamination may have played a role.…”
Section: Accumulation and Abundance Of Microplastics In Aquatic Envir...mentioning
confidence: 99%
“…Even in rural or urban areas, Tibet Plateau had undeniably been tainted with MPs (Jiang et al, 2019). Subsequently, a few studies confirmed that MPs were coming from developed areas with intense human activities and remote areas (Blair et al, 2019;Anak Alexander Tampang and Mohan Viswanathan, 2022).…”
Section: The Ingestion Of Polystyrene By Aquatic Biota Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, for sampling and data collection, vessels of diverse speeds, dimensions, and types are used. Virginia and North Carolina, USA 596-2,224 particles/kg (Dodson et al, 2020) Kelvin River, UK 161-432 items/kg of dry sediment (Blair et al, 2019) Tributaries of Thames River Basin, UK 88-1,190 items/100 g of dry sediment (Lots et al, 2027) Edgbaston Pool, England 26 particles/100 g of dried sediment (Vaughan et al, 2022) Deerness Sound, Orkney, Scotland 5.65 ± 0.55 number of MPs/kg of sediment (Jones et al, 2020) Irish Continental Shelf 7.67 ± 2.09 and 6.33 ± 4.91 MPs/m 3 (Martin et al, 2017) Italy, France, Turkey, Greece, Israel, Bosnia, Portugal, Norway, Denmark, Sweden, Netherlands 72 ± 24 to 1512 ± 187 particles/kg of dry sediment (Lots et al, 2017) Lake Mjøsa and Lake Femunden, Norway 7.31 and 3.89 MPs/g (Lusher et al, 2018) Southern North Sea, Europe 421 particles/kg dry weight of sediment (Maes et al, 2017) River Elbe, Germany 3.35 × 10 6 ± 6.60 × 10 6 particles/m 3 (Scherer et al, 2020) Netherlands and Germany 100-2,071/kg dry weight of sediment (Leslie et al, 2017) Antuã River, Portugal 100-629 items/kg in March and from 18 to 514 items/kg in October (Rodrigues et al, 2018) Eastern Mediterranean, Lebanon 2,433 ± 2,000 MPs/kg d.w of sediment (Kazour et al, 2019) Lagoon-Channel of Bizerte, Northern Tunisia 7.96 ± 6.84 articles/g dry sediment (Abidli et al, 2017) Southeastern coastlines, South Africa 688.9 ± 348.2 particles/m 2 to 3,308 ± 1449 particles/m 2 (Nel et al, 2015) Baltic Sea, Russia 34 ± 10 items/kg dw of sediment (Zobkov and Esiukova, 2017) Mumbai, India 68.83 items/m 2 (194.33 ± 46.32 items/m 2 ) (Jayasiri et al, 2013) Maharashtra, Goa, and Karnataka, India 43.6 ± 1.1 to 346 ± 2 items/m 2 (Maharana et al, 2020) Chennai, Tuticorin, Tiruchenthur, Manapad, and Kanyakumari, India 439 ± 172 to 119 ± 72 items/kg in high tide; 179 ± 68 to 33 ± 30 items/kg in low tide (Sathish et al, 2019) Kanyakumari, India 43 particles/50 g dry sediment (Sundar et al, 2020) Mumbai, Dhanushkodi, and Tuticorin, India 45 ± 12 to 181 ± 60 items/kg (Tiwari et al, 2019) Nallathanni Island, Gulf of Munnar Biosphere Reserve, India NA (Krishnakumar et al, 2018) Nethravathi River, India Sediment: 96 pieces/kg Soil: 84.45 pieces/kg (Amrutha and Warrier, 2020) Sabarmati River, Gujrat, India 47.1 mg (MP in size range 75-212 µm) to 4 mg (MP in size range 212 µm...…”
Section: Water Columnmentioning
confidence: 99%
“…Studies of microplastics in sediments of freshwater environments have indicated that microplastics can be very abundant in urban rivers with high human population density and large commercial and industrial areas (Shruti et al, 2019;He et al, 2020). Microplastics found in these sediments are mainly of secondary origin, arising from the fragmentation of larger plastics or fibers from synthetic clothes washing (Blair et al, 2019). In Amazonian rivers in Brazil, for example, fiber microplastics predominated, especially in the vicinity of the city of urban areas (Gerolin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%